A descriptive study of clinico-epidemiological profile of chronic urticaria from a tertiary care center - Reena Mariyath, Olasseri Kalathingal; Sukumarakurup, Sreekanth; Pinky, Sanjayan Rosamma Roopasree; Ajina, Mohandas; Anagha, Kollarukandy Vijayan (International Journal of Research in Dermatology, 2021)
Background: Chronic urticaria is defined as wheals occurring at least twice weekly for more than six weeks. Exact etiology of chronic urticaria is not known. Only a few studies are available about the clinical and epidemiological profile of chronic urticaria from our part of the country. Methods: A descriptive study was conducted among one hundred consecutives chronic urticaria patients attending the dermatology out patient department of government medical college, Kozhikode to find out the clinical and epidemiological profile of chronic urticaria. Results: Out of 100 patients 25 (25%) were males and 75 (75%) were females with a male to female ratio of 1:3. Angioedema was seen in 63 (63%) patients and dermographism in 53 (53%) patients. Food was the aggravating factor in 34 (34%) patients, exposure to house dust in 28 (28%), sweat in 36 (36%), pressure in 37 (37%), sunlight in 17 (17%), drugs in 22 (22%), stress in 36 (36%), heat in 13 (13%), water in 20 (20%), cold in 5 (5%), infection in 31 (31%) and infestations in 20 (20%) patients. Conclusions: Chronic urticaria is common in females. Angioedema and dermographism are seen in more than half of the patients with chronic urticaria. Most common aggravating factors of chronic urticaria were pressure, sweat, stress, food, infections and exposure to house dust.